Orthodontic pain – the state of the evidence - Cheong, Joo Ming; Tolos, Siti Marponga (IIUM Press, 2022)
Pain is a common side effect of orthodontic treatment. An understanding of its mechanism, implications and subsequent management is essential for any orthodontist to improve patient compliance and satisfaction with treatment. This paper provides a comprehensive review and state of the evidence on orthodontic pain from the viewpoint of clinicians and patients – clinical features, its pathways, factors influencing pain perception, and finally the pharmacological and non-pharmacological management of orthodontic pain.